Desarrollo emocional en niños de 4 años: Modelos pedagógicos y desarrollo cognitivo superior en la escuela "Azogues" cantón Espíndola, periodo 2023 – 2024. - Villamagua Jiménez,Inés Catalina; Correa Guarnizo, Yahaira Sthefany (2024)
The present integration work analyzes the difficulties that 4-year-old children present in terms of higher cognitive development and the influence of the teaching pedagogical model as a possible cause of said problem, therefore, as an objective: Analyze the pedagogical model and its influence on the emotional development and higher cognitive processes in 4-year-old children from the “Azogues” Basic Education School, this study was carried out under a qualitative -quantitative approach, with a descriptive, non-experimental cross-sectional scope; As methods, the scientific, inductive, deductive, analytical and synthetic method was used, the sample was made up of 16 children from initial education II, and a teacher in charge of the grade, as techniques the interview and survey were used and as instruments a interview script and a questionnaire. The results achieved allowed us to understand that the pedagogical practice of the early education teacher shows characteristics of a traditional pedagogical model; Likewise, it is found that the majority of the research sample is at low and medium-low levels in higher cognitive development; In the same way, it is understood that the pedagogical model applied by the teacher significantly influences the higher cognitive development of children. It is concluded that the teacher of four-year-old children applies the traditional pedagogical model in the teaching process, which negatively influences the higher cognitive development of children who present difficulties in these skills. Keywords: Preschool education, critical thinking, learning, pedagogical models, higher cognitive processes.